Effect of Ring Surface Design on the Thrust of a Rotor using in Multirotor UAV - Thai, Thai Son; Vu, Dinh Quy (Old Journal, 2018)
This work employs ANSYS fluent CFD tool to calculate thrust generated a rotor covered by a ring surface using in UAV. The aim of this paper is to characterize the effects of geometry parameters of the ring surface such as diameter and height on the thrust of the rotor. Firstly, the simulations of a full-open rotor at different RPMS is carried out. The results are compared to experiment results to validate the numerical model. Then, the simulations of the rotor covered by a ring surface with different geometry parameters are carried out. The results show that changing diameter of the ring surface leads to thrust generated by rotor also changing. With an increase in the ring surface height thrust increase up to a certain value and stabilizes.